Advances in accounting education : teaching and curriculum innovations - Calderon, Thomas G. (Advances in accounting education, 2019)
And ConclusionsLimitations and Suggestions for Future Research; Recommendations; Length of DC and Mix of Sessions; Research Sessions; Teaching Sessions; Career Management, Networking, and Integration; Enhancing Doctoral Education; Teaching Initiatives; References; Chapter 2: Accounting Department Head: The Road Less Traveled; Background; Method and Demographics; Method; Demographics; Workload Issues; Training; Teaching; Research; Service; Difficulties and Challenges; Compensation/Salary Conversion; Reasons for Becoming a Department Head; Summary and Conclusion; References